DESIGN AND FABRICATION OF A SURFACE pH SENSOR FOR A REAL TIME CORROSION MONITORING - SAEID, KAKOOEI (2013)
The aim of this research is to design and fabricate a new pH sensor that can be used to measure hydrogen ion activity on corroding metal surface in bulk solution or under deposit. Iridium oxide (lrOx) is used for proposed design as pH sensitive material. IrOx is a potentiometric sensor which its open circuit potential regarding a reference electrode is representative of pH.